GUIDED TISSUE REGENERATION IN MAXILLOFACIAL SURGERY - Benetti, Francine [UNESP] (2020)
The regeneration of oral tissues depends on the body’s natural capacity and the materials and techniques currently available. Bone loss in the cranio-maxillo-facial region because of trauma, anatomical or congenital causes, cancer, and bone disease requires surgical intervention. The proposed techniques include treatment with bone grafts, bone substitutes, distraction osteogenesis and guided tissue regeneration (GTR), as well as their combinations. Research in this area has been advancing. The most recent developments in tissue engineering and stem cell and gene therapy have been used in the maxillofacial surgery with good results. Tissue engineering can be divided into conductive, inductive, and cell transplantation modes. GTR is a conductive technique. This procedure, which uses biomaterials to facilitate the growth or regeneration of already existing tissue, entails using a resorbable or non-resorbable membrane that excludes undesirable types of tissue growth and permits only bone cells to populate the surgically treated site, thus guiding the whole regeneration process. Among the indications for the use of GTR technique in maxillofacial surgery are oronasal fissures requiring surgical treatment, oro-antral communication, maxillary sinus lift, increasing the height and thickness of insufficient alveolar ridge for the placement of endosseous implants and prosthetic rehabilitation, and maxillary and mandibular bone changes that require appropriate aesthetic and functional reconstruction. Depending on the size and location of the defect, various surgical techniques for bone regeneration have been described in the literature. The choice of appropriate treatment is a difficult and complex process. The technique of GTR is feasible with good prognosis, when used properly following the basic requirements for the correct application of the membranes. Over the past several years, new concepts and materials have been developed with the aim of increasing the therapeutic arsenal of professionals employing tissue regeneration therapies. This chapter will describe the use of GTR techniques in maxillofacial surgery, as well as the materials used in this procedure and different experimental models studied.